2019
DOI: 10.3390/ma12142323
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Bacterial Cellulose Reinforced with Natural Rubber

Abstract: Films of bacterial cellulose (BC) reinforced by natural rubber (NR) with remarkably high mechanical strength were developed by combining the prominent mechanical properties of multilayer BC nanofibrous structural networks and the high elastic hydrocarbon polymer of NR. BC pellicle was immersed in a diluted NR latex (NRL) suspension in the presence of ethanol aqueous solution. Effects of NRL concentrations (0.5%–10% dry rubber content, DRC) and immersion temperatures (30–70 °C) on the film characteristics were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 40 publications
5
36
0
2
Order By: Relevance
“…The objectives are combined into a global desirability function (D) (Eq. (14)) which reflects the desirable ranges for each response (d i ) from 0 to 1 with n number of measures. The shape of the desirability for each goal varies according to its weight (wt i ) field.…”
Section: Numerical Optimization Using Response Surface Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objectives are combined into a global desirability function (D) (Eq. (14)) which reflects the desirable ranges for each response (d i ) from 0 to 1 with n number of measures. The shape of the desirability for each goal varies according to its weight (wt i ) field.…”
Section: Numerical Optimization Using Response Surface Methodsmentioning
confidence: 99%
“…In the past, Le-Moigne et al [13] used two-parameter Weibull approach to assess fiber particle size distribution and shape parameters of natural fibres after compounding in composites; the particle sizes distribution of natural rubber was investigated by Potivara and Phisalaphong [14] using laser diffraction technique; Zhang et al [15] also used particle size analyzer to examine the effect of particle size distribution on properties of bio-composites, authors found that surface roughness, specific surface area and size of natural fibre particles has significant influence on mechanical interlocking, interfacial diffusion and mechanical properties of the composites. Despite the useful results so far reported, these post production assessment of particle size distribution however limits the designer's locus of control over critical material and process factors influencing mechanical properties of reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…All reports of BNC in emulsion polymerization involve first polymerizing polymer particles (or purchasing commercial latexes) and then subsequently blending BNC into the water phase. To date, blending of BNC with polymers such as poly (hydroxyoctanoate), [242] poly(butyl acrylate-co-methyl methacrylate), [243] carboxylated acrylonitrile-butadiene rubber, [244,250] natural rubber, [245,247,249] and styrene-butadiene rubber [246,248] (all relatively low glass transition temperature, T g , polymers) have been shown to reinforce the polymer nanocomposites cast from dispersion. In most reports, the polymer particle diameter is not reported but typical sizes are listed in Table 4.…”
Section: Bnc In Emulsion and Suspension Polymerizationmentioning
confidence: 99%
“…Pemanfaatan selulosa bakteri dibidang kesehatan sudah cukup banyak penelitiannya, diantaranya: sebagai kulit buatan untuk luka bakar, pembuluh darah buatan, dan teknik penyembuhan luka (Potivara &Phisalaphong, 2019). Selain itu terdapat beberapa hasil penelitian pemanfaatan selulosa bakteri di bidang farmasi, kususnya kosmetik, diantaranya: penggunaan selulosa bakteri sebagai masker matriks wajah (Muhsinin et al, 2017), penstabil emulsi (Jia et al, 2016) matriks pembawa obat (Potivara &Phisalaphong, 2019), dan bahan alternatif dalam pembuatan cangkang kapsul (Ullah et al, 2017).…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian selulosa bakteri dapat diproduksi dalam berbagai media asalkan media tersebut minimal harus memiliki sumber nitrogen, karbon, makro, dan mikronutrient yang diperlukan untuk pertumbuhan mikroorganisme seperti fosfor, belerang, kalium, dan magnesium (Das &Dash, 2020). Selulosa bakteri yang dihasilkan dilakukan pengujian karakterisasi untuk mengetahui kualitasnya (Potivara &Phisalaphong, 2019). Karakterisasi selulosa bakteri dapat meliputi 6 pengujian yakniX-Ray Difraction (XRD), thermogravimetricanalysis(TGA), FTIR Fourier Transform Infrared Spectroscopy (FTIR), Water Absorption, Mechanical Properties, Scanning Electron Microscopy (SEM) (Shimpi, 2018).…”
Section: Pendahuluanunclassified